Analysis of approaches to develop of the competents system of the project team of the building company virtual logistic center creation - Antypenko, Yevgen; Ivko, Andrii (Technology audit and production reserves, 2017)
The object of research is the system of development of individual and organizational competence in the project of creating a virtual logistics center of a construction company. One of the most problematic places is the lack of systematic approach in construction organizations for development of personnel, the improvement of organizational competencies and the formation of technological maturity in the field of project management. To address these shortcomings, the project considers the filling of 28 competencies according to the model of the International Project Management Association. Based on the models of the International Project Management Association and Harold Kerzner, a combined model for development of organizational and individual competencies is proposed. In the model, the levels of technological maturity in the field of project management are aligned with the main elements of competencies inherent in the levels, as well as the main values. The tasks that the system for managing the development of the competence of the project team for creating a virtual logistics center for a construction company should be formulated. In the course of the study, the method of analyzing international standards and the synthesis method for constructing a combined model was used. An effective mechanism for the associated development of individual and organizational competencies in the construction organization is obtained. This is due to the fact that the proposed combined model has a number of features, in particular, system, the interconnectedness of individual and organizational elements of competence, the existence of a value dimension. Thanks to this, it is possible to increase the efficiency of organizational activities of construction organizations as a result of using the model by 10–15 %. In comparison with similar known models, this provides such advantages as: the interconnected development of individual and organizational competencies, the value measurement of competence and the possibility of constructing an integral value-competence strategy for the development of a construction organization.